A brief history of thrift - Hulme, Alison (Manchester University Press, 2019)
This book surveys 'thrift' through its moral, religious, ethical, political, spiritual and philosophical expressions, focussing in on key moments such as the early Puritans and post-war rationing, and key characters such as Benjamin Franklin, Samuel Smiles and Henry Thoreau. The relationships between thrift and frugality, mindfulness, sustainability, and alternative consumption practices are explained, and connections made between myriad conceptions of thrift and contemporary concerns for how consumer cultures impact scarce resources, wealth distribution, and the Anthropocene. Ultimately, the book returns the reader to an understanding of thrift as it was originally used -- to 'thrive' -- and attempts to re-cast thrift in more collective, economically egalitarian terms, reclaiming it as a genuinely resistant practice.